NARRATIVE REVIEW ON SARCOMAS AND POSTOPERATIVE INTERVENTIONS IN THE LOWER EXTREMITIES - Vasconcelos Vieira Siqueira, Viviane; Luís Lopes Gomes de Siqueira, André (Health and Society, 2023)
The treatment and rehabilitation of soft tissue sarcomas and osteosarcoma of the lower extremities have gained increasing attention in oncology medicine. The importance of subjective and objective measures in assessing postoperative outcomes, the effectiveness of chemotherapy regimens in non-metastatic osteosarcomas, and the relevance of exercise interventions for rehabilitation after sarcoma surgery were explored. Additionally, insights into return to sport after musculoskeletal tumor surgeries and details of the tibial turn-up procedure were presented. This review emphasizes the need for an interdisciplinary approach to optimize patient outcomes.